Case Report: Insights into multiple cases of Pseudomyxoma peritonei - Chu, HanJie; Song, XiaoBiao (Frontiers in Gastroenterology, 2025)
As a rare peritoneal malignant tumor, Pseudomyxoma peritonei (PMP) is a challenge in the field of surgery and oncology due to its complex pathological mechanism and difficult clinical management. Although the comprehensive treatment regimen centered on cell reduction (CRS) combined with intraperitoneal hyperthermic chemotherapy (HIPEC) has significantly improved the prognosis of patients, postoperative recurrence is still common, and repeated recurrence cases are particularly rare, and its clinical characteristics and treatment strategies need to be further explored. In this paper, the clinicopathological features, recurrence patterns and treatment difficulties of PMP were systematically analyzed by reviewing an elderly patient with three relapses and operation and combining with the data of four cases with different disease course. Through multi-case discussion and literature review, this study aims to provide clinicians with a more comprehensive understanding of the disease, optimize individualized treatment decisions, and provide references for further exploration of the molecular mechanism and novel therapeutic targets of PMP.